2021
DOI: 10.3390/bios11120519
|View full text |Cite
|
Sign up to set email alerts
|

Development, Optimization, Characterization, and Application of Electrochemical Biosensors for Detecting Nickel Ions in Food

Abstract: Nickel is naturally present in drinking water and many dietary items, which expose the general population to nickel ingestion. This heavy metal can have a variety of harmful health effects, causing allergies and skin disorders (i.e., dermatitis), lung, cardiovascular, and kidney diseases, and even certain cancers; therefore, nickel detection is important for public health. Recent innovations in the development of biosensors have demonstrated they offer a powerful new approach over conventional analytical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Carbon-based electrodes are widely used in electroanalytical investigations for the development of sensors to determine organic and inorganic analytes because of their low cost, good electron transfer kinetics, and biocompatibility [ 36 , 40 ]; moreover, modification of the carbonaceous surface is necessary to improve the electrocatalytic potential for the oxidation of organic and inorganic hydroperoxides. Urease is a nickel-dependent enzyme found in many organisms, including algae, fungi, prokaryotes, and plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Carbon-based electrodes are widely used in electroanalytical investigations for the development of sensors to determine organic and inorganic analytes because of their low cost, good electron transfer kinetics, and biocompatibility [ 36 , 40 ]; moreover, modification of the carbonaceous surface is necessary to improve the electrocatalytic potential for the oxidation of organic and inorganic hydroperoxides. Urease is a nickel-dependent enzyme found in many organisms, including algae, fungi, prokaryotes, and plants.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on nickel biosensor development reported that urease affixed to SPEs was effective for nickel detection in food samples [ 36 ]. Using the same dynamic range from the previous study, we furthered the work by optimizing receptor immobilization agents with four biopolymers types and concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nickel, a widely used transition metal in industrial production, is also an essential micronutrient distributed throughout the human body. It mainly exists as divalent ions and plays a vital role in numerous enzymes ( Genchi et al, 2020 ; Anchidin-Norocel et al, 2021 ). Nickel ions are found in various tissues such as the liver, kidney, spinal cord, brain, heart, cartilage, lung connective tissue, and skin ( Afzali and Mohammadi, 2011 ; Rajivgandhi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%